ECONOMIES OF SCALE AND TECHNICAL EFFICIENCY OF SMALLHOLDER PEPPER (Capsicum species) PRODUCTION , ABUJA, NIGERIA. - Olugbenga, Alabi Omotayo (Journal of Agricultural Sciences (Belgrade), 2022)
This study examined economies of scale and technical efficiency of smallholder pepper (Capsicum species) production in Abuja, Nigeria. The study was designed to achieve the following specific objectives: identify the socio-economic characteristics of smallholder pepper producers, estimate the costs and returns of smallholder pepper production, evaluate factors influencing output of smallholder pepper production, evaluate factors influencing technical efficiency of smallholder pepper production, determine the technical efficiency index of smallholder pepper producers, determine the elasticity of production and economies of scale of smallholder pepper production, and identify the constraints facing smallholder pepper producers. Multi-stage sampling technique was used to obtain a total sample size of 100 smallholder pepper farmers. Primary data were obtained from pepper producers through the use of a well-designed and structured questionnaire. The data were analyzed using descriptive statistics, gross margin model, financial analysis, Stochastic Frontier Model, elasticity of production, the return to scale, and principal component analysis. The results from the study show that the mean age observed was 38.3 years. About 80% of the smallholder pepper producers were male and 74% of them were married. The average family size was 5 persons.The gross margin was N 167, 741.60 per hectare, the rate of returns of the investment in pepper production amounted to 2.17, and the operating ratio was 0.49. The gross margin ratio was 0.48, this implies that for every one naira that is invested in smallholder pepper production, 48 kobo covered profits, expenses, taxes, and depreciation. Labour input (P < 0.10), seed input (P < 0.01), farm size (P < 0.01) were significant factors influencing output of smallholder pepper production in the study area. In the technical inefficiency model, level of education (P < 0.05), household size (P < 0.01), and access to extension agent (P < 0.01) were statistically significant. The mean technical efficiency was 0.79 leaving a gap of 0.21 for improvement. The constraints facing smallholder pepper farmers were: use of crude implements, lack of fertilizers, lack of improved seeds, lack of extension services, pest, diseases insurgence and infestation, lack of credit facilities, bad road infrastructures, lack of access to farm land, and lack of information. The retained constraints explained 70.32% of the variations of the component included in the model. The study concluded based on the findings that smallholder pepper production was a profitable enterprise. The study recommends that policies that will encourage smallholder pepper production be formulated and implemented. Also, measures are put in place to address the challenges of inadequate rainfall through proper irrigation policies.